Optimalisasi Peran Bumdes dalam Pemberdayaan Ekonomi Berkelanjutan Desa Haruyan Dayak Kecamatan Hantakan Kabupaten Hulu Sungai Tengah - Adnina, Rania; Budhi, Setia; Sa'diah, Halimatus; Fatimah, Siti; Sembiring, Philips Silwanus Elifiel; Hermawan, Hery; Fatahilah, Muhammad Ibnu; Mustakimah, Wafiq; Panjaitan, Klara Septari; Aziza, Wafiq; Suhasti, Indri (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Haruyan Dayak Village has abundant natural potential, especially in banana plantations, but unfortunately does not have the space to utilize these potentials, as well as several obstacles in an effort to utilize these natural products, such as relatively low selling prices, many middlemen and others. BUMDes is also present as a forum for boosting the economy at the village level. Village-owned enterprises, or often called BUMDes, are institutions established by the village government that function as economic drivers at the village level. BUMDes Adi karya Bina Warga is a BUMDes that was established in Haruyan Dayak Village in 2024, this revitalized BUMDes is expected to be a foundation that can help village communities in utilizing existing potentials so as to improve community welfare, in the implementation of this BUMDes revitalization, many steps must be taken by the Pengabdi team until this BUMDes can be re-established. The implementation of this program was carried out for 58 days, starting from July 18, 2024 to September 13, 2024, in Haruyan Dayak Village, Hantakan District, Hulu Sungai Tengah Regency. This data collection was carried out through observation, interviews, direct participation, and documentation. The service team also used the live-in method to build relationships with local communities in order to find out firsthand what the Haruyan Dayak village community really needs, this journal provides an overview of the development of BUMDes conditions starting from the beginning of its formation and analyzes its development strategy at BUMDes in Haruyan Dayak Village, so that BUMDes can return with management who are ready to run business units that have been formed and designed together with BUMDes administrators and the service team.